AB0145 EFFECTS OF IMMUNOSUPPRESSIVE MEDICATION ON TYPE I INTERFERON ACTIVATION: IN VITRO ANALYSIS SHOWS A DOWNREGULATING EFFECT ON IFN ACTIVATION OF HYDROXYCHLOROQUINE AND ASPIRIN. (13th June 2020) - Wahadat, M. J.; Lourens, M.; Huijser, E.; Van Helden-Meeuwsen, C. G.; Kamphuis, S.; Versnel, M.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is prototypic Interferon (IFN) driven autoimmune disease characterized by an increased expression of type-I IFN stimulated genes, known as the IFN signature. The inhibitory effects of various drugs like Hydroxychloroquine and more recently Aspirin on IFN inducing pathways (1, 2) led to the idea that some standard of care drugs might decrease the IFN score in patients. Data on the in vitro effect of immunosuppressive medication on IFN activation are limited. Testing immunosuppressive agents for their effect on IFN activation in vitro will give insight into the mechanisms of IFN activation in vivo and the effect of immunosuppressive medication on this activation. Objectives: To study the effect of immunosuppressive medication on the type-I IFN signature in an in vitro model Methods: Freshly isolated human PBMCs were stimulated for 24 hours with or without CpG-A or Imiquimod (IQ) or transfected with the cGAS agonist G3-YSD to induce IFN upregulation through the TLR7/9- and DNA Sensing Receptor-pathway respectively. To assess the direct role of the medication on the downstream pathway of the IFNAR PBMCs were stimulated with IFN-a2b. Aspirin, diclofenac, HCQ, Mycophenolate Mofetil (MMF) and prednisone were added separately to these cultures followed by analysis of MxA by qPCR as a readout for IFN type I activation. Cell viability in all culture conditions was above 85%. Results: The type I IFN activation induced by CpG-A, IQ, G3-YSD and IFN-a2b was significantly reduced after addition of Aspirin. Addition of diclofenac showed a trend towards reduced levels in all conditions. HCQ was able to significantly reduce the TLR7/9 induced IFN activation by CpG-A and IQ while MMF and prednisone did not show an effect in any of the culture conditions. Conclusion: The IFN activation induced by the stimulation of various IFN inducing pathways was significantly reduced by Aspirin and HCQ in an in vitro model. Combining both clinical and in vitro data from our longitudinal cohort of childhood-onset SLE patients will elucidate the effect of different immunosuppressive drugs on the type-I IFN signature in these patients. References: [1]Kuznik A, Bencina M, Svajger U, Jeras M, Rozman B, Jerala R. Mechanism of endosomal TLR inhibition by antimalarial drugs and imidazoquinolines. J Immunol. 2011;186(8):4794-804. [2]Dai J, Huang YJ, He X, Zhao M, Wang X, Liu ZS, et al. Acetylation Blocks cGAS Activity and Inhibits Self-DNA-Induced Autoimmunity. Cell. 2019;176(6):1447-60 e14. Disclosure of Interests: None declared